Diversity and Ginsenoside Biotransformation Potential of Cultivable Endophytic Fungi Associated With Panax bipinnatifidus var. bipinnatifidus in Qinling Mountains, China - An, Chao; Ma, Saijian; Shi, Xinwei; Liu, Chen; Ding, Hao; Xue, Wenjiao (Frontiers in Pharmacology, 2022)
To obtain novel fungi with potent β-glucosidase for minor ginsenosides production, Panax bipinnatifidus var. bipinnatifidus, which is a traditional medicinal plant containing various ginsenosides, was firstly employed to isolate endophytic fungi in this study. A total of 93 representative morphotype strains were isolated and identified according to ITS rDNA sequence analyses and were grouped into three phyla (Ascomycota, Basidiomycota, Mucoromycota), five classes (Dothideomycetes, Sordariomycetes, Eurotiomycetes, Agaricomycetes, Mucoromycetes), and 24 genera. Plectosphaerella (RA, 19.35%) was the most abundant genus, followed by Paraphoma (RA, 11.83%) and Fusarium (RA, 9.70%). The Species Richness Index (S, 34) and the Shannon-Wiener Index (H’, 3.004) indicated that P. bipinnatifidus harbored abundant fungal resources. Twenty-six endophytic fungal ethyl acetate extracts exhibited inhibitory activities against at least one pathogenic bacterium or fungus. Eleven strains showed strong β-glucosidase activities and also presented ability of ginsenoside biotransformation with varied glycoside-hydrolyzing pathways. Excitingly, three genera of Ilyonectria, Sarocladium, Lecanicillium and all 11 taxa were firstly found to have the ability to transform ginsenosides in our study.The results indicated that P. bipinnatifidus could be a new fungi resource with potential novel natural compounds with antimicrobial activity and potent β-glucosidase for varied minor ginsenosides production.